PERJUANGAN TOKOH EMANSIPASI PEREMPUAN INDONESIA DAN JERMANFahmi WahyuningsihFakultas Bahasa dan Seni, Universitas Negeri Surabaya (Lentera, Jurnal Studi Perempuan, 2013)
Abstract Many things can be discussed and debated from noble of Gods creatures called "women" . There are many issues that can be discussed and there are many female characters who can be an inspiration in the fight for emancipation. In Indonesia we have RA Kartini, in Western German, we have socialist Clara Zelkin that could be used as inspiration to achieve equal rights between women and men who fought for by women more than a century ago. This is the main objective of the centenary of International Womens Day or International Womens Day (IWD) on March 8, 2010. This event, marks the worldwide womens international agreement to fight for a world free from distinctions of class, race and gender. Women’s struggle to fight for equality still becomes a long journey to fight for, even in todays global era. Key words: Struggle, Spirit, and the nature of Women